Language as a mental travel guide. (19th June 2020) - Davis, Charles P.; Altmann, Gerry T. M.; Yee, Eiling
Abstract: Gilead et al.'s approach to human cognition places abstraction and prediction at the heart of "mental travel" under a "representational diversity" perspective that embraces foundational concepts in cognitive science. But, it gives insufficient credit to the possibility that the process of abstraction produces a gradient, and underestimates the importance of a highly influential domain in predictive cognition: language, and related, the emergence of experientially based structure through time.